Siamese Melting Pot Ethnic Minorities in the Making of Bangkok - Van Roy, Edward ([S.l.] : ISEAS - Yusof Ishak Institute, 2017)
Ethnic minorities historically comprised a solid majority of Bangkok's population. They played a dominant role in the city's exuberant economic and social development. In the shadow of Siam's prideful, flamboyant Thai ruling class, the city's diverse minorities flourished quietly. The Thai-Portuguese; the Mon; the Lao; the Cham, Persian, Indian, Malay, and Indonesian Muslims; and the Taechiu, Hokkien, Hakka, Hainanese, and Cantonese Chinese speech groups were particularly important. Others, such as the Khmer, Vietnamese, Thai Yuan, Sikhs, and Westerners, were smaller in numbers but no less significant in their influence on the city's growth and prosperity. In tracing the social, political, and spatial dynamics of Bangkok's ethnic pluralism through the two-and-a-half centuries of the city's history, this book calls attention to a long-neglected mainspring of Thai urban development. While the books primary focus is on the first five reigns of the Chakri dynasty (1782-1910), the account extends backward and forward to reveal the continuing impact of Bangkok's ethnic minorities on Thai culture change, within the broader context of Thai development studies. It provides an exciting perspective and unique resource for anyone interested in exploring Bangkok's evolving cultural milieu or Thailand's modern history.
Siamese Melting Pot: Ethnic Minorities in the Making of Bangkok -- Contents -- List of Maps -- List of Tables -- Preface -- 1. Old Bangkok: An Ethnohistorical Overview -- 2. Interlopers: Portuguese Parishes -- 3. Safe Haven: Mon Refugees -- 4. Under Duress: Lao War Captives -- 5. Contending Identities: Muslim Minorities -- 6. Taming The Dragon: Chinese Rivalries -- 7. Along the Margins: Some Other Minorities -- 8. Retrospect: Contextualizing Some Contentious Concepts -- Bibliography -- Index -- About the Author.
Includes bibliographical references and index.
Keywords: Minority Studies